Penerapan Case Based Reasoning Dalam Memprediksi Masa Tunggu Kerja Calon Alumni - Abdul Rahman; Pujianto; Joko Kuswanto (STMIK Budi Darma, 2023)
Alumni are assets for an educational institution, can illustrate how the vision and mission of the alumni home institution are achieved. Educational institutions need to track their graduates, this is done as a source of information and to find out the absorption, process, and position of graduates in the world of work and assist government programs in mapping the needs of the world of work with competencies obtained from universities. In addition, to increase the accreditation of a university, college or department. So important is alumni data in the world of work, there is a need for a system to predict the waiting points for alumni to work. The purpose of this study is to apply the Case Based Reasoning in predicting the waiting period of prospective alumni at Baturaja University using the K-Neareast Neigbor algorithm. Reasoning is based on 14 attributes with 10 rule bases. Based on the representation of the new case, the similarity value of the old case with the new case is 0.64